Religious Insurgency and Quest for Sustainable Peace in Nigeria: The Islamic Model as a Panacea - Lawal, Manzoor Apenna; Dauda, Kazeem Oluwaseun (Dialogia, 2023)
The religious insurgency championed by the Boko Ḥarām movement has threatened Nigeria's quest for sustainable peace for more than a decade despite the counter-insurgency measures of successive governments. This paper examined Nigeria's turbulent decade of religious insurgency, its position within the Islamic context, and Islamically-inclined practicable solution to the threat. It used analytical research method based on existing secondary literature and primary Islamic law sources. The paper reveals that a turbulent decade of Boko Ḥarām insurgency has wreaked havoc on the peace and tranquillity previously existing among Nigeria's diverse ethno-religious entities. The analysis of Quranic texts, aḥādīth and opinions of notable scholars also indicates that religious insurgency associated with Boko Ḥarām is inconsistent with Islamic doctrines. Tolerance among religionists, proper religious teachings and interpretation of divine scripture, genuine inter and intra-faith dialogues, Islamic leadership-cum-governance paradigms, among others, were the identified Islamic-modelled panacea to the insurgency. The paper concludes that if the identified Islamic model can be embraced and considered in the scheme of things by religious and political leaders, as well as their ardent followers, the current religious insurgency would be drastically curtailed, thereby advancing sustainable peace in Nigeria.